Marine ecological security assessment from the perspective of emergy ecological footprint - Wang, Cui; Lin, Aiyong; Liu, Conghu (Frontiers in Marine Science, 2023)
Introduction Marine ecological security assessments are considered as a basis for coordinating marine economic development and ecological protection. Methods We propose an assessment method based on the emergy ecological footprint which first measures the emergy of the natural and economic elements of the marine ecosystem. Considering the role of economic, social and waste discharge factors in the marine ecosystem, an ecological security evaluation index is constructed, and a dynamic evaluation is conducted based on long time series data to characterize the change trend of ecological security. Results The Guangxi marine ecosystem was selected as the case study, and the ecological security dynamic evaluation was conducted by collecting data from 2008 to 2020. The results show that Guangxi's marine ecosystem has always been in an ecologically secure state, but since 2010, the emergy ecological footprint intensity has been increasing, indicating ecosystem deterioration. Therefore, some targeted suggestions are put forward. Discussion This method provides a new assessment tool for marine ecological security evaluation and offers guidance for the sustainable development and utilization of marine ecosystems.